MEREDUKSI PERILAKU BLINDISM MELALUI KEGIATAN PRKTIKUM MENGGUNAKAN BEAKER GLASS BRAILLE PADA PENGUASAAN KONSEP PENGUKURAN VOLUME - FATHUR RIZKI, M (Jurnal Pendidikan Khusus, 2017)
Abstract: The impact of impairment on causing children to experience problems in behavior that is not in accordance with normal children in general. Behaviors such unusual behavior called blindism. Blindism behavior have an impact on a lot of things, especially in the academic field so that learning becomes less than the maximum. The purpose of this study was to determine the condition of the child when the child is not given the intervention (A), intervention (B) and the tendency of the stability of the phase of the baseline (A) to the intervention phase (B) through practicum activities using glass beaker braille on command  concept of volume measurement . This study uses a quantitative approach to research the type of experiment Singgle Subject Reseach (SSR) with A-B design, the number of subjects is one (1) class blind children 7 SMPLB-A YPAB Surabaya. Technique of collecting data in the form of observation method. The result of data analysis show that through practicum activity measuring the volume of  regular and irregular object can reduce the behavior of blindism wiggle the bodies of children with visual impairment Keywords: Blindism, Practicum, Visual Empairment.